Compressed oil palm fronds composite: a preliminary study on mechanical properties - Mohd Sukhairi Mat Rasat; Razak Wahab; Amal Najihah Muhamad Nor; Sitti Fatimah Mhd. Ramle; Mahani Yusoff; Siti Aisyah Nawawi (IJSciences, 2013)
The mechanical properties of composites consisting of compressed oil palm fronds have been investigated. Three maturity groups at different portion were bind together using two types of formaldehyde resin which were phenol and urea. Modulus of rupture (MOR) for bending strength of the compressed oil palm fronds composite increase from young to intermediate and mature maturity group for each portion, meanwhile decrease from bottom to middle and top portion for each maturity group. Same results trend have been recorded for modulus of elasticity (MOE) for bending strength and modulus of rupture (MOR) for compression strength. Statistical analysis indicated significant differences between compressed oil palm fronds composite made from each maturity group and portion, but no differences were observed in the type of resin used.